1997
DOI: 10.1007/bf01254252
|View full text |Cite
|
Sign up to set email alerts
|

[123I]β-CIT single-photon emission tomography in Parkinson's disease reveals a smaller decline in dopamine transporters with age than in controls

Abstract: [123I]beta-CIT single-photon emission tomography in Parkinson's disease reveals a smaller decline in dopamine transporters with age than controls Tissingh, G.; Bergmans, P.; Booij, J.; Winogrodzka, A.; Stoof, J.C.; Wolters, E.CH.; van Royen, E.A. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
3
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
8
3
1
Order By: Relevance
“…We did not find significant correlation between age and binding of [ 123 I]‐FP‐CIT in the striatum or any subregion, but others have found a negative correlation in healthy volunteers(Pirker et al. , 2000) and in patients with PD(Tissingh et al. , 1997).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We did not find significant correlation between age and binding of [ 123 I]‐FP‐CIT in the striatum or any subregion, but others have found a negative correlation in healthy volunteers(Pirker et al. , 2000) and in patients with PD(Tissingh et al. , 1997).…”
Section: Discussioncontrasting
confidence: 73%
“…, 1997). The correlation with age is not consistent(Tissingh et al. , 1997) and the disease severity exceeds age when it comes to affecting the binding of the marker in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, several PET and SPECT radioligand binding studies have reported that DAT decreases with age (Volkow et al . 1994, 1996; Tissingh et al . 1997; Volkow et al .…”
Section: Presynaptic Daergic Markers In Striata Of Adultsmentioning
confidence: 99%
“…[ 123 I]β-CIT and [ 123 I]FP-CIT SPECT have a high discriminative power to differentiate PD from normal aging as shown in Figure 7, particularly when the DAT availability in the putamen is evaluated Tissingh et al, 1998). Similar results with a sensitivity and specificity between 95 and 100% have been obtained with [ 99m Tc]TRO-DAT-1 (Weng et al, 2004), suggesting that the three radioligands are equally sensitive in detecting the DA deficit at an early stage of PD.…”
Section: Diagnostic Biomarkermentioning
confidence: 99%